Internalization of Anti-corruption Education Values as Formation of Honest Character for PIPS IPI Students - Ilmi Rizkiani Sundara, Ilmi Rizkiani Sundara; Eldi Mulyana; Triani Widyanti; Alni Dahlena (SAHUR Journal, 2024)
Talking about honest character is the same as talking about one of the ultimate goals of learning anti-corruption education, especially for students of Social Sciences Education, Indonesian Institute of Education. Students of Social Sciences Education, Indonesian Institute of Education, before completing anti-corruption education lessons, still have a dishonest attitude. To overcome this problem, it is necessary to internalize the values ​​of anti-corruption education which must be applied to students so that they have an honest character as they should. Internalizing the values ​​of anti-corruption education as the formation of honest character is good enough to be applied to students of Social Sciences Education, Indonesian Institute of Education. The purpose of this research is to describe the internalization of anti-corruption educational values ​​as the honest character formation of Social Sciences Education students, Indonesian Institute of Education. The method used in this research is qualitative with a case study approach. Data collection techniques in this study used observation, interviews and documentation. The results of this study indicate that 1) the values ​​of anti-corruption education are able to instill a better honest character in students who have completed learning anti-corruption education courses 2) the efforts made by students vary but are carried out with small habits by instilling honest character 3) internalization of anti-corruption educational values ​​is able to produce the formation of honest character possessed by social science education students, Indonesian Institute of Education.